EVALUATION OF A GIRL WITH 16p13.11 MICRODUPLICATION SYNDROME ACCORDING TO THE INTERNATIONAL CLASSIFICATION OF FUNCTIONING, DISABILITY AND HEALTH PERSPECTIVES - Fidan, Hande; Kerem Günel, Mintaze; Haliloğlu, Göknur; Ütine, Gülen Eda; Kiper Şimşek, Pelin Özlem (Sanamed, 2022)
Objective: To present the functional status of a child with 16p13.11 microduplication syndrome by evaluating it under the International Classification of the World Health Organization’s International Framework for Functioning, Disability and Health (ICF). Case Description: An 11-year-old girl with 16p13.11 microduplication syndrome was assessed using the tools classified according to ICF for Children and Youth (ICF-CY) categories to evaluate body function, activity participation, and environmental factors.There was a wide range of problems, from body functions to activity participation and environmental factors. Besides these problems, there were social and cognitive disorders as well. Conclusion: Physical and cognitive problems in body function and activity together constitute great barriers to participation in daily life.